Motor control system and material direction of belt conveyor on Dosimat Feeder based on IoT with ESP32 at PT Semen Padang - Rinaldi, Thaufik Qurrhahim; Mirshad, Emilham (Journal of Industrial Automation and Electrical Engineering, 2025)
Uneven material distribution on the dosimat feeder belt conveyor at PT Semen Padang causes the belt to tilt, resulting in material spillage and decreased production efficiency. To address this issue, an Internet of Things (IoT)-based control system was designed to detect belt tilting and automatically guide the material back to the center of the belt. This system utilizes an ESP32 microcontroller, a load cell sensor to read load distribution, four limit switches (two for detecting tilting and two for detecting material that veers off the track), two servo motors to direct material from the right and left sides, and a buzzer to provide an alert when material goes off the track. Real-time monitoring is conducted through the Blynk platform. Testing results showed that the load cell sensor had an average error of 1.68%, with the highest error of 3.3% at a 100-gram load and the lowest error of 1.17% at 200 and 400 grams. The limit switches for tilt detection were activated at an 85-gram load to trigger the servo, while the limit switches for material off-track were activated at a 100-gram load to stop the system and activate the buzzer. This system has proven effective in reducing material loss and improving production efficiency.